A review on the application of activity-based costing and time driven activity-based costing in manufacturing industry - Nurul Farahin, Zamrud; Abu, Mohd Yazid; Nik Nurharyantie, Nik Mohd Kamil; Filzah Lina, Mohd Safeiee; Oktaviandri, Muchamad (2019)
Activity-based costing (ABC) and Time-Driven Activity-based Costing (TDABC) are example of costing structures that bring benefits to an organization and it is supported by numerous published papers. However, it is acknowledged that there is no report on comparison of ABC and TDABC on product costing in manufacturing industry. Therefore, the purpose of this study is to examine the research gap of ABC and TDABC in manufacturing industry. There are 130 of published papers on ABC and TDABC from period 2011-2018 to be analyzed. Through the application of ABC, it improves effectiveness, helps in decision making process and provides information for critical analysis. Furthermore, TDABC overcomes the limitations of ABC and it provides an accurate costing process. It promotes direct allocation and represents accurate unused capacity.